STRATEGIC OF EMPOWERING GREEN INVESTMENT REGIME THROUGH DEVELOPING POTENTIAL OF MARINE TOURISM IN WEST NUSA TENGGARA PROVINCE - SH, Nurasmah (Jurnal IUS, 2015)
The objective of the research is to know and to analizy the existence ofÂ green investment regime through developing of the marine tourism in Indonesia, especially in Lombok; optimalized strategic and institution role for green investment; and to integrated of the sustainable regulation for green investment. The typical of the research is normative â empirical study. The approaches that used in this research are conceptual approach, statute approach and empirical approach as a supportedÂ approach. The result of the research shows that, first, conceptually, green investment regime is a part of green economy as a mainstream to develop investment especially in developing of marine tourism. Second, the strategic to optimalyze institution for green investment could be implemented through the general and special strategic. At the local level, the strategic of institutional empowering could be implemented by empowering of region resources management and social, economic and culture empowering. Third, internalization of the economic instrument aspect in to environmental management aspect could be follow by the green economic, so as the regulation of the investment priority not only economic oriented but also considerÂ environment aspect. The recomendations that can be proposed based on research result are , first, green investment regime is an ideal concept should be necessary embodying in investment practice in local area. It means that all of stakeholder required a good perception and understanding related to investment activity in local area. Second, it needs clarity strategic, program and the output must be concrete and the operational related to the management design to develop marine tourism in Lombok. Third, in order to create an optimal strategy, an effective and efficent development of Green Investmen,t its required a legal regulation in form of local government regulation on Marine Investment. Â Keywords: Green Investment, Marine Tourism.